KUALITAS HIDUP ANAK DENGAN DOWN SYNDROME DI YAYASAN POTADS (PERSATUAN ORANG TUA ANAK DENGAN DOWN SYNDROME) JAWA BARAT - OCHE AXENA YULHAN; ISRA THRISTY (JURNAL ILMIAH KOHESI, 2021)
Down syndrome is a congenital disorder characterized by an excess number of chromosome 21. Down syndrome affectsone in 700 births or one in 800-1,000 births and it is estimated that there are currently eight million people with DownSyndrome worldwide. A child with Down Syndrome is special because the excess chromosome results in changes of thephysical characteristics and intellectual abilities, as well as disturbances in physiological functions, which will affect thechild's independence and quality of life. To determine the quality of life in children with Down Syndrome based on age, sex,adaptive function, type of disease experienced, behavioral problems based on parental support. His study uses aquantitative descriptive method with a cross sectional design. The population in this study were all children with DownSyndrome who have joined the West Java POTADS (Parents Association of Children with Down Syndrome) foundation, withtotal of 300 people. This study shows that children with Down Syndrome aged 6-15 years have the lowest average quality oflife score on the feeling aspect (1.75) and the highest on the cognitive aspect (2.90). Quality of life for children with DownSyndrome can be seen from age, gender, parental support, as well as from children’s social and healt problem.